2014
DOI: 10.4236/jcdsa.2014.41001
|View full text |Cite
|
Sign up to set email alerts
|

Skin Hydrating Effects of <i>Corchorus olitorius</i> Extract in a Mouse Model of Atopic Dermatitis

Abstract: Background: Corchorus olitorius leaf contains a significant amount of mucilaginous polysaccharide. It has been generally accepted that the polysaccharides derived from botanical extracts increase skin hydration. Since skin hydration improves skin barrier function, it is one of the most effective treatments for atopic dermatitis (AD). However, other components of botanical extracts other than polysaccharides may influence skin hydration and transepidermal water loss (TEWL). The aim of this study was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Our previous study showed that the COEE cream increased the skin hydration and reduced the TEWL on the AD-like skin lesions in NC/Nga mice, and protected the skin barrier function in these mice. Further, the COEE cream improved the AD symptoms, and suppressed the increases in the AD score in NC/Nga mice [10]. We hypothesized that COEE might be effective against AD.…”
Section: Introductionmentioning
confidence: 94%
“…Our previous study showed that the COEE cream increased the skin hydration and reduced the TEWL on the AD-like skin lesions in NC/Nga mice, and protected the skin barrier function in these mice. Further, the COEE cream improved the AD symptoms, and suppressed the increases in the AD score in NC/Nga mice [10]. We hypothesized that COEE might be effective against AD.…”
Section: Introductionmentioning
confidence: 94%
“…Wound healing is the process by which the skin and other soft tissues are repaired following injury. Authors Yokoyama et al (2014) investigated the skin hydration on atopic dermatitis in mice using C. olitorius leaf extract excluding high MW (COEW), and the results show a possible therapeutic benefit for atopic dermatitis due to decreased plasma immunoglobulin E (IgE) level as well as mast cell degranulation [ 145 ]. In this study, mice treated with the COEW cream experienced significantly increased skin hydration and reduced transepidermal water loss (TEWL) compared with control mice, but IgE concentrations were not affected, whereas NC/Nga mice showed a decreased AD score.…”
Section: Biological Activitymentioning
confidence: 99%
“…This concluded that the plant may maintain the hydration of the skin and inhibit the disturbance of skin barrier function, therefore, it could be used as a complementary therapy in atopic dermatitis. 44 An atopic dermatitis mouse model was used to assess the skin hydration capacity of C. olitorius extract. The extract was combined with a stable base cream and applied to the mice's dorsal skin.…”
Section: Wound Healing Propertymentioning
confidence: 99%
“…This concluded that the plant may maintain the hydration of the skin and inhibit the disturbance of skin barrier function, therefore, it could be used as a complementary therapy in atopic dermatitis. 44 …”
Section: Pharmacological Biodiversitymentioning
confidence: 99%